Análise do tema bullying em revistas femininas para adolescentes - Maia, Ana Cláudia Bortolozzi [UNESP]; Pastana, Marcela [UNESP] (My University, 2014)
Practices of violence such as physical and verbal aggression, provocations, humiliations and exclusion that occur mainly among young people in schools are named as bullying and the aim of this qualitative-descriptive study was to investigate how this phenomenon is represented by magazines directed to teenage girls. The analysis was conducted in fifteen articles of four Brazilian magazines: Capricho, Todateen, Atrevida and Yes Teen through thematic categories: 1) Definitions and explanations about bullying; 2) Magazines’ proposals to the confrontation against bullying (2.1 Campaigns and orientations against bullying; 2.2 Advices about how to act in the presence of bullying; 2.3 Examples of “overcoming” to people who suffered bullying and 2.4 Advices given to people who practice bullying). It was identified the presence of hierarchies, stereotypes and the incentive to competition. There is the predominance of normative and excluding patterns, advices that individualize the issue and lack of critical reflection.

Prácticas de violencia como agresiones físicas y verbales, provocaciones, humillaciones y exclusiones que ocurren principalmente entre jóvenes en las escuelas son llamadas de bullying y el objeto de este estudio cualitativo-descriptivo fue investigar cómo este fenómeno es representado por las revistas dirigidas a las chicas adolescentes. El análisis se realizó en 15 materias de cuatro revistas brasileñas: Capricho, Todateen, Atrevida y Yes Teen a partir de categorías temáticas: 1) Definiciones y explicaciones sobre el bullying; 2) Propuestas de las revistas para el enfrentamiento del bullying (2,1 Campañas y orientaciones contra el bullying, 2.2 Consejos sobre cómo actuar frente al bullying, 2.3Ejemplos de “superación” para quien sufrió bullying y 2.4 Consejos dados a quien practica el bullying). Se identificó y discutió la presencia de jerarquías, estereotipos y del incentivo a la competición. Hay la predominancia de patrones normativos y excluyentes, consejos que individualizan la cuestión y la ausencia de reflexión crítica.

Práticas de violência como agressões físicas e verbais, provocações, humilhações e exclusões que ocorrem principalmente entre jovens nas escolas são chamadas de bullying e o objetivo deste estudo qualitativo-descritivo foi investigar como este fenômeno é representado pelas revistas direcionadas para garotas adolescentes. A análise foi realizada em 15 matérias de quatro revistas brasileiras: Capricho, Todateen, Atrevida e Yes Teen a partir de categorias temáticas: 1) Definições e explicações sobre o bullying; 2) Propostas das revistas para o enfrentamento do bullying (2.1 Campanhas e orientações contra o bullying, 2.2 Conselhos sobre como agir diante do bullying, 2.3 Exemplos de "superação" para quem sofreu bullying e 2.4. Conselhos dados a quem pratica o bullying). Foi identificada e discutida a presença de hierarquias, estereótipos e do incentivo à competição. Há a predominância de padrões normativos e excludentes, conselhos que individualizam a questão e ausência de reflexão crítica. Palavras-chave: Bullying. Mídia. Adolescência.
Analysis of the theme bullying in feminine magazines for teens
Análisis del tema bullying en revistas femeninas para adolescentes
Keywords: Bullying; Mídia; Adolescencia; Bullying; Media; Adolescente